Mike Wakelam: an appreciation. Issue 3 (10th July 2020) - Michell, Bob
Abstract: This issue of Essays in Biochemistry explores lipid mediators — biologically active metabolites formed by enzymic and non-enzymic oxidation of polyunsaturated fatty acids. These can be exported across the cell membrane into the extracellular space, where they activate cell surface receptors to stimulate the cells of origin (autocrine) or nearby cells (paracrine). Lipid mediators are involved in many physiological processes, which may become dysregulated during ageing and in lipid-related diseases such as diabetes, atherosclerosis, arthritis, cancer, Alzheimer's disease and metabolic syndrome. Following the death in March 2020 of Professor Mike Wakelam, with the loss of his major input into the lipid signalling field, Portland Press and Guest Editors John Harwood and Emyr Lloyd-Evans decided to dedicate this issue to his memory. This Editorial briefly recalls his work and influence.